PENGARUH KEAKTIFAN BERORGANISASI TERHADAP MOTIVASI BELAJAR SERTA IMPLIKASINYA TERHADAP PRESTASI BELAJAR - Riska Mustika Sari; Ai Nur Solihat; Ati Sadiah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of organizational activeness on learning motivation and its implications for learning achievement. The research method used is survey method with explanatory design. The population in this study were students who were members of student councils in public high schools in Tasikmalaya City, totaling 204 students. The sampling technique used random sampling. The data collection technique was carried out through a questionnaire and the analysis technique used was path analysis. The results showed that there was a positive and significant influence between organizational activeness on learning motivation, there was a positive and significant influence between organizational activeness on learning achievement, and there was a positive and significant influence between organizational activeness on learning achievement through learning motivation.